Evaluation accuracy, repeatability and performance of Galileo and Beidou positioning in Antarctica region - Pirti, Atinc; Bakula, Mieczyslaw; Eren, Mehmet (TAYLOR & FRANCIS LTD, 2026)
Growing activities in the Antarctica call for more navigation and positioning services in this region. The current GNSS (Global Navigation Satellite System) constellations, which have the capability of fully global positioning services, consist of GPS, GLONASS, Galileo and BeiDou. At higher latitudes, GNSS signal degradation due to ionospheric activity is more pronounced. The more precise phase-based positioning modes are particularly vulnerable to ionosphere disturbance such as scintillations. Elevated ionospheric activity can cause a loss of precise-positioning mode or, in more extreme cases, a total loss of signal lock. Monitoring the movement and evolution of ice shelves and glaciers as well as geodetic prospecting requires highly precise positioning. Galileo-only static processing (OPUS-Beta) can provide millimetre-to-centimetre accuracy for the long baselines in this study.
Keywords: Galileo; BeiDou; Multi-GNSS; Antarctica; Accuracy; ROSS SEA; MESOSCALE CYCLOGENESIS; AMBIGUITY RESOLUTION; GPS; PROBABILITY; Engineering; Geology; Remote Sensing